Building School Brand Image Through Internal Branding and Islamic Branding in an Integrated Islamic Primary School: A Qualitative Case Study with Embedded Descriptive Survey Data from SDIT Tawakkal Pacitan - M. Ibnu Ahmad; Arif Mustofa (MyResearch ID Publishing, 2025)
Purpose – This study aims to explain how SDIT Tawakkal Pacitan builds and maintains brand image as an elementary school that integrates modern science and Islamic values, as well as how middle-class Muslim perceptions shape their preferences toward the school.Methods/Design/Approach – The research uses a case study with a qualitative approach strengthened by embedded descriptive quantitative data. Qualitative data were collected through semi-structured interviews with the principal, vice principal, homeroom teachers, and parents/guardians; observation of school activities; and document analysis. Quantitative data were obtained through a parent questionnaire to map the socioeconomic profile and the weight of decision factors. Qualitative analysis followed an interactive model of reduction, display, and verification, with source and method triangulation.Findings – Parents interpret the brand image of SDIT Tawakkal as a religious, smart, and noble-character elementary school, as reflected in the consistency of services, an integrated curriculum, habituation of worship, teacher role modeling, and school-home partnerships. Questionnaire results show that the dominant factor of preference is the unique value of the integration of aqliyah and ruhiyah education (65,5%), followed by the school environment (16,8%), teacher quality (11,5%), and aqidah alignment (6,3%). The principles of Islamic branding operate as a normative foundation through the integration of aqidah, sharia, and akhlak in service design and school culture.Originality/Value – This study affirms that the brand image of SDIT in local nonmetropolitan contexts is primarily shaped by internal branding and the coherence of the service experience, not promotion alone.Practical Implications – SDIT managers need to position branding as a quality strategy by standardizing services based on unique values, aligning teacher recruitment and development with the school’s identity, and maintaining school-home partnerships in an accountable manner and sensitive to privacy.Keywords brand image, internal branding, integrated Islamic school, middle-class Muslims, Islamic branding.Paper type Research paper